Progesterone Modulation of Pregnancy-Related Immune Responses - Shah, Nishel M.; Imami, Nesrina; Johnson, Mark R. (Frontiers in Immunology, 2018)
Progesterone (P4) is an important steroid hormone for the establishment and maintenance of pregnancy and its functional withdrawal in reproductive tissue is linked with the onset of parturition. However, the effects of P4 on adaptive immune responses is poorly understood. In this study, we took a novel approach by comparing the effects of P4 supplementation longitudinally, with treatment using a P4 antagonist mifepristone (RU486) in mid-trimester pregnancies. Thus, we were able to demonstrate the immune-modulatory functions of P4. We show that, in pregnancy, the immune system is increasingly activated (CD38, CCR6) with greater antigen-specific cytotoxic T cell responses (granzyme B). Simultaneously, pregnancy promotes a tolerant immune environment (IL-10 and regulatory-T cells) that gradually reverses prior to the onset of labour. P4 suppresses and RU486 enhances antigen specific CD4 and CD8 T cell inflammatory cytokine (IFN-γ) and cytotoxic molecule release (granzyme B). P4 and RU486 effectively modulate immune cell-mediated interactions, by regulating differentiated memory T cell subset sensitivity to antigen stimulation. Our results indicate that P4 and RU486, as immune modulators, share a reciprocal relationship. These data unveil key contributions of P4 to the modulation of the maternal immune system and suggests targets for future modulation of maternal immune function during pregnancy.